Seasonal and Latitudinal Response of New Zealand Sea Surface Temperature to Warming Climate Since the Last Glaciation: Comparing Alkenones to Mg/Ca Foraminiferal Reconstructions. Issue 11 (29th November 2019) - Sikes, Elisabeth L.; Schiraldi, Benedetto; Williams, Amanda
Abstract: Dual proxies were used to estimate paleo sea surface temperatures (SST) for the Bay of Plenty, north of New Zealand. U 37 K ′ and Mg/Ca in the planktonic foraminifera Globogerina bulloides reconstruct SST for the growth seasons for the organisms they are based upon. U 37 K ′ SST (summer) were consistently ~ 3.5 °C warmer than Mg/Ca (spring), suggesting that Bay of Plenty SST during the last glacial maximum (LGM) was 17.3 °C in summer and 13.8 °C in spring. Combining these results with published data based on the same proxies from other sites around New Zealand shows cooling of 3–4 °C in both seasons at all sites in the LGM relative to the Holocene. This indicates that overall, glacial surface water cooling was similar in subtropical and subpolar waters in both spring and summer. This contrasts with published foraminiferal assemblage reconstructions suggesting greater subantarctic cooling during the LGM. Deglacial warming across the region was characterized by changes in both seasonal and latitudinal temperature differences. Warming began in subtropical waters at ~21 ka, ~ 1.5 ka earlier than in subantarctic water. In the Bay of Plenty, the seasons maintained a consistent offset, while in Hawke Bay, springs stayed cold while summers warmed until after the Antarctic Cold Reversal. In contrast, subantarctic spring SST warmed rapidly, causing temperature differences to decrease between the Chatham Rise (subantarctic) and subtropical sites, possibly caused by shifting westerly winds. The use of multiple proxies enhances our understanding by adding a seasonal component to the glacial story of climate change in the southwest Pacific Ocean. Key Points: Alkenone and foraminiferal Mg/Ca provide seasonal temperature reconstructions for late winter/early spring versus summer in the New Zealand area Sea surface temperatures were 3–4 °C cooler in both seasons during the last glaciation in both subtropical and subantarctic waters Significant changes in seasonality and latitudinal gradients in SST were only seen during the deglaciation from 35 to 45°S around New Zealand